2010
DOI: 10.1177/1073191110370116
|View full text |Cite
|
Sign up to set email alerts
|

The Dutch Memory Compensation Questionnaire

Abstract: The Memory Compensation Questionnaire (MCQ; de Frias & Dixon, 2005) is a psychometrically sound instrument which assesses the variety and extent to which an individual compensates for actual or perceived memory losses. Until now, only an English version of the MCQ has been psychometrically evaluated. The aim of the present study was to establish a Dutch version of the MCQ and evaluate its psychometric properties. The MCQ data of N=556 cognitively healthy adults (61.8% females) aged between 50.1 and 95.3 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…The results of the present study showed that the factor structure of the French version is consistent with the factor structures that were obtained in English-, Spanish-, and Dutch- speaking samples (see de Frias & Dixon, 2005; Van der Elst et al, 2011), supporting the cross-national robustness of the MCQ. The expected seven factors underlie the item responses of the French version of the MCQ (i.e.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The results of the present study showed that the factor structure of the French version is consistent with the factor structures that were obtained in English-, Spanish-, and Dutch- speaking samples (see de Frias & Dixon, 2005; Van der Elst et al, 2011), supporting the cross-national robustness of the MCQ. The expected seven factors underlie the item responses of the French version of the MCQ (i.e.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, pattern of correlations were consistent with the English- and Dutch- versions: all scale scores of the French adaptation were positively correlated with each other (see Table 3); as well as with the total score of the MCQ (all r > .45, p<.01). Findings indicate that individuals use more than one type of strategies which fit with Van der Elst et al (2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations